Paracrine regulation of theca androgen production by granulosa cells in the ovary - Hoang, Yvonne D.; McTavish, Kirsten J.; Chang, R. Jeffrey; Shimasaki, Shunichi (Fertility and sterility, 2013)
To test whether and to what extent inhibin mediates Cyp17 messenger RNA (mRNA) expression in theca cells (TCs) in response to FSH stimulation of granulosa cells (GCs). Ex vivo and in vitro experimental study. University. Immature female Sprague Dawley rats. Ovarian tissue explants and isolated theca cell preparations with or without GCs were treated with FSH, inhibin, inhibin antibody, or β-glycan antibody. As a key enzyme in androgen production, Cyp17 mRNA levels were measured by real-time reverse transcription–polymerase chain reaction. After 24 hours, Cyp17 mRNA expression was dose-dependently increased by FSH in ovarian tissue explants and theca cells, suggesting that paracrine factor(s) secreted from GCs in response to FSH mediates Cyp17 mRNA expression in TCs. Antibodies against inhibin and inhibin coreceptor, β-glycan, blocked the stimulatory effect of FSH on Cyp17 mRNA expression. However, inhibin alone did not increase Cyp17 mRNA level to the same extent. These findings suggest a role for inhibin in the paracrine regulation of TC Cyp17 mRNA expression by GCs influenced by FSH; however, other paracrine factors produced by GCs by virtue of FSH seem to be required.